Formation of dimers delayed alginate degradation in fecal microbiota fermentation - Yuan, Dan; Xiao, Wenqian; Tao, Xingyu; Gao, Zhiming; Wu, Yuehan; Jiang, Wenxin; Li, Yanlei; Ni, Xuewen; Zhou, Mengzhou (Carbohydrate polymers, 2025)
The present study was to examine the dimer formation of two alginate chains and its degradation in gut microbiota using an in vitro colon fermentation model. The most rapid degradation stage of guluronate in alginate was from 6 h to 24 h (1.68 μg/mL/h), while guluronate in dimers was from 24 h to 36 h (1.69 μg/mL/h). The degradation extent of alginate (97.40 %) was remarkably higher than that of dimers (84.20 %) in 48 h fermentation. Fecal microbiota randomly cleaved alginate into discrete mannuronate blocks (M-blocks), guluronate blocks (G-blocks), or M/G G-blocks. In contrast, dimers were sequentially cleaved into M-blocks before the crosslinked G-blocks. Approximately 25 % of crosslinked G-blocks survived the 48-h fermentation. Furthermore, three Bacteroides spp. strains could collaboratively degrade M-blocks and then crosslinked G-blocks in dimers sequentially. Collectively, the crosslinked G-blocks impeded the dimer degradation by fecal microbiota, presenting a slower degradation rate and a lesser degradation extent. [Display omitted] •Two alginate molecule chains paired into a dimer under R (Ca2+/G) =0.25.•Dimers were degraded by fecal microbiota at a slower rate and to a lesser extent.•The M-blocks were cleaved before the G-blocks in dimers.•Twenty-five percent of crossed G-blocks in dimers survived the fermentation.•Three Bacteroides spp. collaboratively degraded dimer structures.